Highly thermally conductive and insulating composites fabricated through the hot-pressing of hollow structured h-BN/rGO hybrid filler - Cho, Jangwoo (2024)
Polymer composites have several advantages: affordability, ease of processing, and versatile applications. In this study, hexagonal boron nitride (h-BN)/epoxy spheres were fabricated using NaCl, then washing away the NaCl with water to create h-BN/epoxy hollow structures. Reduced graphene oxide (r-GO) was subsequently wrapped around these structures to produce h-BN/r-GO/epoxy hollow structures. These structures were then fabricated into composites through a hot pressing method involving high pressure and heat, which achieved a vertical alignment of the h-BN components to establish a heat transfer path, with r-GO evenly dispersed throughout. The thermal conductivity of the h-BN/r-GO/epoxy composite was measured as 4.12 W/m·K, representing a 2060 % increase compared to that of neat epoxy. Despite incorporating electrically conductive r-GO, the h-BN/r-GO/epoxy composite maintained its insulating properties. This is attributed to the even distribution of insulating h-BN within the h-BN/r-GO/epoxy hollow structures.